The role and importance of the institution of mediation in the mechanism of alternative dispute resolution - X.T.Odilqoriev (Zien Journals, 2022)
The article considers with the emergence of legislative foundations of mediation, meaning of the concept, history of formation, essence, principles, stages and classification issues.
Keywords: Mediation; alternative dispute resolution; main principals of mediation; agreement of mediation